Micro Changes : A Process Perspective on Organizational Change. - Bruskin, Signe; ProQuest (firma) (New York : Oxford University Press, Incorporated, 2025)
Micro Changes is a book about the changes we experience at work. Typically, the changes that influence our well-being the most are the ones that change something in our everyday work, such as getting a new leader, another IT program, shifting from face-to-face meetings to online, or simply the office coffee taste different. These are micro changes, and the book aims to unfold what they look like in practice, why they are essential, and how to handle them. The book is a mix of examples and cases from practice, process theories, and reflection exercises that inspire how to work with micro changes in the future.
Part III Organizational Changes in Practice -- 9 Concepts of Practice -- Implementation of organizational changes -- Change successes -- Employee involvement -- Resistance to change -- Employee engagement -- Psychological safety and micro changes -- Summary of chapter -- Dialogue tool: Radical changes to the individual -- 10 The Role of the Change Leader -- Change leadership -- The role of change agents -- Change facilitation -- Handling of change -- Paradoxes in organizational changes -- The strategic change leader -- Summary of chapter -- Reflection exercise: Personal experience of radical changes -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books